In vitro synthesis of the unit that links teichoic acid to peptidoglycan. - Hancock, I (1976)
The role of cytidine diphosphate (CDP)-glycerol in gram-positive bacteria whose walls lack poly(glycerol phosphate) was investigated. Membrane preparations from Staphylococcus aureus H, Bacillus subtilis W23, and Micrococcus sp. 2102 catalyzed the incorporation of glycerol phosphate residues from radioactive CDP-glycerol into a water-soluble polymer. In toluenized cells of Micrococcus sp. 2102, some of this product became linked to the wall. In each case, maximum incorporation of glycerol phosphate residues required the presence of the nucleotide precursors of wall teichoic acid and of uridine diphosphate-N-acetylglucosamine. In membrane preparations capable of synthesizing peptidoglycan, vancomycin caused a decrease in the incorporation of isotope from CDP-glycerol into polymer. Synthesis of the poly (glycerol phosphate) unit thus depended at an early stage on the concomitant synthesis of wall teichoic acid and later on the synthesis of peptidoglycan. It is concluded that CDP-glycerol is the biosynthetic precursor of the tri(glycerol phosphate) linkage unit between teichoic acid and peptidoglycan that has recently been characterized in S. aureus H.